Pašvērtējuma, apmierinātības ar dzīvi un agresijas atšķirības pieaugušajiem ar un bez bērnībā pieredzētas vecāku šķiršanās - Ekarte, Marika (Latvijas Universitāte, 2013)
Pētījuma mērķis ir noskaidrot vai pastāv atšķirības starp uzrādītajiem pašvērtējuma, apmierinātības ar dzīvi un agresijas rādītājiem respondentiem ar bērnībā pieredzētu vecāku šķiršanos un respondentiem bez vecāku šķiršanās pieredzes, kontrolējot dzimumu. Pētījuma mērķa noskaidrošanā pielietota pašvērtējuma aptauja (Rosenberg Self-Esteem Scale, RSE, Rosenberg, 1965), apmierinātības ar dzīvi aptauja (Satisfaction with life scales. Diener, 1985), agresijas līmeņa noteikšanai - agresijas aptauja (The Aggression Questionnaire, Bruss & Perry, 1992). Saskaņā ar pētījuma rezultātiem, statistiski nozīmīgas atšķirības starp abām grupām pastāv apmierinātības ar dzīvi rādītājos, savukārt dzimumatšķirības pastāv agresijas aptauju rādītājos. Atslēgas vārdi: pašvērtējums, apmierinātība ar dzīvi, agresija

The goal of the research is to find out if there are differences between the demonstrated levels of self-esteem, satisfaction with life and aggression in respondents having experienced divorce of their parents in childhood and respondents without parents’ divorce experience, discriminating also by gender profile. The following methods were used for purposes of the research goal – survey of self-esteem (Rosenberg Self-Esteem Scale, RSE, Rosenberg, 1965), survey of satisfaction with life (Satisfaction with life scale. Diener, 1985), and aggression questionnaire to determine the level of aggression (The Aggression Questionnaire, Buss & Perry, 1992). The results of the research indicate statistically significant differences between both groups regarding their levels of satisfaction with life, and reveal differences from the gender aspect in the questionnaire measuring aggression. Key words: self-esteem, satisfaction with life, aggression
Differences in self-esteem, life satisfaction and aggression in adults with and without experience of parents' divorce in childhood
Keywords: Psiholoģija